2007
DOI: 10.1590/s0066-782x2007000200012
|View full text |Cite
|
Sign up to set email alerts
|

Reprodutibilidade da medida ambulatorial da pressão arterial em pacientes hipertensos com diabete melito tipo 2

Abstract: Mean of pressure levels measured by ABPM presented good reproducibility and were not affected by placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Except in the case of comparing baseline DBP with that at 4 months (71.8%), the concordance in the classification of the dipper pattern between measurements is no higher than 70% and even considering those classified as extreme dippers or risers the pattern may change. Previous publications have reported figures for reproducibility that are similar to those found in our study or slightly lower 29,31,33 . Omboni et al observed a reproducibility of 60.3% considering SBP and 60.9% considering DBP 18 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Except in the case of comparing baseline DBP with that at 4 months (71.8%), the concordance in the classification of the dipper pattern between measurements is no higher than 70% and even considering those classified as extreme dippers or risers the pattern may change. Previous publications have reported figures for reproducibility that are similar to those found in our study or slightly lower 29,31,33 . Omboni et al observed a reproducibility of 60.3% considering SBP and 60.9% considering DBP 18 …”
Section: Discussionsupporting
confidence: 90%
“…Previous publications have reported figures for reproducibility that are similar to those found in our study or slightly lower. 29,31,33 Omboni et al observed a reproducibility of 60.3% considering SBP and 60.9% considering DBP. 18 Gorostidi et al 34 and at Booth et al study 35 noted that the nondipper pattern is more common and the reproducibility is slightly higher in high-risk patients than in other groups.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main problems is the necessity of validation studies of each oscillometric device. We recently tested and retested the Spacelabs - 90207 automatic cuff-oscillometric devices (Spacelabs, Inc. Redmond, WA-USA) in hypertensive type 2 diabetic patients [28] and we found that it is a reliable method to clinical management of those patients. An obstacle that remains is the high price and limited availability of 24-h ABPM devices in general practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings with more than three missing hours (maximum of 1 h during the night) were excluded from the analysis. Visit-to-visit BP coefficients of variation are 2–5% (16,17). …”
Section: Methodsmentioning
confidence: 99%